Incidence and Type II Diabetes Mellitus Risk Factors in Chronic Hepatitis Type C Affected Patients - Kuldeep Poorani, Mohammad Amjad Kalhoro, Atif Ahmed, Kashif Ali, Safia Bano, Bedar Bakhat Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Type II diabetes is common among patients with chronic hepatitis C. The aim of the study is to govern the risk factors and prevalence of type II diabetes mellitus in chronic hepatitis C patients. Place and Duration: The study was held among 100 patients with chronic hepatitis C enrolled in the Liver Clinic of Bilawal Medical College Hospital Kotri one-year duration from January 2019 to January 2020. Methods: This is a cross-sectional study in which 100 patients with chronic hepatitis C virus who encountered the exclusion and inclusion principles were selected. Sex, height, age, smoking history, weight, body mass index and family history of diabetes were recorded, blood pressure was measured, and serum transaminase, total bilirubin, and albumin were tested. The analysis of the data was done using SPSS 23.0 statistics. The chi-square test was applied. Results: Hundred patients with chronic hepatitis C were selected for the study, 58(50%) were male and 42 (42%) were female (Fig. 1). While the number of diabetic patients among HCV patients was 24 (30%), 56 patients (70%) had chronic hepatitis C without diabetes. The study group age varies from 32 to 73 years, with the mean being 45.42 ± 9.15. 52 of the 100 patients were under 45 years of age (13 diabetic, 39 non-diabetic). In contrast, 48 patients were over 45 years of age (21 diabetics, 27 not). In the study group, family history with diabetes was positive in 35 (35%) of 100 patients, with diabetes and HCV in 21 and in 14 HCV without diabetes. The smoking history was positive in 33 (33%) of the 100 patients in the study group. The total number of subjects with less than 30 kg / m2 BMI were 62 (62%) and patients with a body mass index above 30 kg / m2 were 38. Conclusion: Aging, elevated BMI and diabetes mellitus family history are considered risk factors for developing type-II diabetes mellitus in chronic hepatitis C affected patients.